Moisture contribution of the Atlantic Warm Pool to precipitation: a Lagrangian analysis - Sorí, Rogert; Drumond, Anita; Nieto, Raquel (Frontiers in Environmental Science, 2015)
In this work we use a Lagrangian model (FLEXPART) to investigate the contribution of moisture from the Atlantic Warm Pool (AWP) to the atmospheric hydrological budget during the period from 1982 to 1999, and to identify which regions are affected by the moisture transport from this source. FLEXPART computes budgets of evaporation minus precipitation by calculating changes in the specific humidity along 10-day forward trajectories. A monthly analysis was made for May-October, the typical development period of the AWP. Climatologically, the moisture transported from the AWP to North and Central America increases from June onwards. Humidity is also transported towards western Europe from July to October, probably favoured by the positioning of the North Atlantic Subtropical High and its associated flows. The largest moisture sinks associated with transport from the AWP were found from August to October, when the warm pool can extend to the north-western coast of Africa. The technique of composites was used to analyse how the interannual variability of moisture contribution from the AWP depends on changes in the pool’s areal extension, and on the El Niño Southern Oscillation (ENSO). The results indicate that during episodes when the AWP is at its maximum extent, its moisture contribution increased to the Caribbean, to the region of the Inter-tropical Convergence Zone (ITCZ), and to the North Atlantic. By contrast, less moisture was transported to southeastern North America during July and August, or to central North America during September and October. The differences in moisture sink regions for extreme ENSO episodes suggest that there are favoured sinks in the Caribbean and in the ITCZ region during La Niña events.